Islamic approach toward purification of transaction with cryptocurrency - Al-Hussaini, Nigeria; Ibrahim, Adamu Abubakar; Noordin, Mohamad Fauzan; Mohd Mohadis, Hazwani (Journal of Theoretical and Applied Information Technology, 2020)
This paper presents a qualitative study that examine the perception of users on Islamic approach toward purification of transaction with cryptocurrency. Bitcoin is has been used as a case study which is one of the type of cryptocurrency. There are huge discrepancies from many Islamic school of thought about transaction with bitcoin. Specifically, some school of thought viewed it as a tool used for illegal purposes and that the global public already uses Bitcoin mostly for illegal and non-Shari’ah-compliant purposes under Islamic perceptions. As a result, this study developed an interview-qualitative research approach in order to examine how the negative perceptions of cryptocurrency from Islamic views cnd be purify. Sample of Eight informant were used in the study. The finding of this study indicated that the use of cryptocurrency as a legitimate as any payment method. It is also argued that it facilitated transactions and cut the normal cost of international money transfer, and some Muslim countries are actively encouraging the use of cryptocurrency due to its easy use and transparency. This has been also supported by “hadith”. Finally, the analysis also confirmed that from the Shari'ah point of view, cryptocurrencies are as compliant as fiat money and ought to be accepted as another mode of payment that can be used in transaction as its value can be measured and quantified. Therefore, this study has contributed in understanding the Islamic views behind the implementation of cryptocurrency.